If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 120 = 60t Solving 120 = 60t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-60t' to each side of the equation. 120 + -60t = 60t + -60t Combine like terms: 60t + -60t = 0 120 + -60t = 0 Add '-120' to each side of the equation. 120 + -120 + -60t = 0 + -120 Combine like terms: 120 + -120 = 0 0 + -60t = 0 + -120 -60t = 0 + -120 Combine like terms: 0 + -120 = -120 -60t = -120 Divide each side by '-60'. t = 2 Simplifying t = 2
| 130=60t | | 150=60t | | 5g*5g= | | 5a-9=3a+5 | | 160=60t | | 6x-1=34 | | -8q=634 | | -n-6=21 | | 209-u=134 | | 7h-12=10h-12-3h | | 99a=176 | | 4x+3(-7x+4)= | | 341m=500 | | 2+3(2x+1)=19 | | 54r=29 | | 93+8x=102+7x | | 6w+8-3w=2w-6 | | 222=-u+118 | | 155s=249 | | 3(n+3)+5n=36 | | 3=-3n | | 5n^2+33n+18=0 | | 89b=113 | | 217c=335 | | 4z+6-7=7 | | .05(200-d)+.10=14.00 | | 2(x+4)+2x=20 | | 5r*8s= | | 81p=9 | | -11m=220 | | 45r=17 | | N+5=7+8 |